The Appointment of Non-Muslim Leaders (Study of Surah Al-Mâ'idah verses 51 and 57 Using Semantic Approach) - Umum Budi Karyanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
It is a common thing that there is a controversy over non-muslim leadership in the majority of muslims. Historically, this issue has been long-standing and has always been debatable among experts from time to time. As the result of this issue,Ulamas are divided into two groups, one of them is forbid the non-muslim issue, but others permit. Indonesia, which has muslim as the most population often experience a collision related to the appointment of non-muslim leaders. Essentially, leadership is a mandate that must be mandated to those who can afford it. Indonesian law guarantees all its citizens to emerge as both muslim and non-muslim leaders. Therefore, this paper attempts to analyze the appointment of non-Muslim leaders with a semantic approach according to verses of the Qur'ân that textually prohibit muslims (believers) to appoint non-muslims as leaders. It is because of the words waliy and auliyā'which textually have the meaning as